Study of influence of combined argon-arc surfacing on quality of antifriction layer (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
This work is devoted to the issues of obtaining a high-quality coating of aluminum bronze Br AMts 9-2 on low-carbon steel by double-arc (combined) argon-arc surfacing with a non-consumable tungsten electrode, as well as the study of the properties of these coatings, which determine the possibility of their use as materials with antifriction properties in the manufacture and restoration of friction parts and assemblies. The analysis showed that most surfacing methods do not provide the possibility of obtaining high antifriction properties of the bronze coating in one pass. It is proven that the use of a combined double-arc method of surfacing, which allows for flexible regulation of the amount of heat input into both the base and the additive material, eliminates the main problems of obtaining a high-quality bronze coating, such as, first of all, cracks at the “steel-bronze” fusion boundary, the presence of which reduces the reliability of the antifriction layer. Welding stresses and deformations in the surfacing layer are one of the decisive factors determining the quality and performance of the antifriction layer. To justify the choice of the method for determining residual stresses and deformations in the surfacing layer, modern research methods have been analyzed. It has been established that all existing methods for determining welding stresses and deformations use different hypotheses that simplify the real processes of elastoplastic deformation during surfacing (welding). To measure residual stresses, the method of measuring deformations of the stressed state disturbed by a hole was used. Displacements were determined by measuring with a laser-computer interferometric system that records interferometric lines of the displacement level of significant areas of the body surface in the zone of disturbing influence (the place of application of force or the probing hole). This allows us to visually determine the main directions of the strain and stress tensors, and to draw qualitative conclusions about the distribution of stresses. The conducted studies showed that the average level of residual stresses after repeated electric arc treatment decreased slightly, their redistribution occurred more quickly. Studies of the antifriction properties and wear resistance of hardened parts showed that the use of this manufacturing technology allows replacing cast pistons with bimetallic ones.
Keywords: antifriction layer; cracks; residual stresses; deformations; double-arc surfacing; heat input